2021
DOI: 10.25077/jom.6.1.58-65.2021
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors For The Occurrence of Low Birth Weight Based on Nutritional Status of Pregnant Women With Upper Arm Circumference

Abstract: The nutritional status of pregnant women before and during pregnancy can affect the growth of the fetus in the womb. The purpose of this study was to look at the risk factors of  LBW events based on nutritional status based on the MUAC size of pregnant women. This research is analytical with cross sectional study design by sampling using the total sampling technique of 98 pregnant women in Kubang Village, Sukaresmi District, Cianjur Regency. Analyze data using Chi Square. Univariate analysis results from 98 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Age is a significant factor in determining LBW. Healthy young women showed a balanced diet for developing fetuses [21].…”
Section: Resultsmentioning
confidence: 99%
“…Age is a significant factor in determining LBW. Healthy young women showed a balanced diet for developing fetuses [21].…”
Section: Resultsmentioning
confidence: 99%
“…Mothers who took food less than two times had a 2 times higher chance of delivering LBW babies [ 15 ]. In another study, the nutritional status of pregnant women revealed that mothers who had experienced malnutrition during their pregnancies were more likely to give birth to underweight children [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women who suffered from chronic lack of energy and babies born with LBW will cause growth and development disorders. [23][24] The risk of growth restriction would be exacerbated if the incidence of malnutrition in the fetus was followed by inadequate food intake in the first two years of life. 21 Research conducted by Aobama and Purwito shows that mothers who had a history of CED during pregnancy will affect the growth process of the baby in the womb.…”
Section: Discussionmentioning
confidence: 99%